In-Hosptal Outcome and Angiographic Findings in Acute Inferior Myocardial Infarction with ST-Segment Elevation in Posterior Chest Leads ( V7, V8, V9 ) Following Thrombolytic Therapy (Bangladesh Heart Journal, 2017)
Background: Electrocardiographic diagnosis of a posterior wall myocardial infarction is difficult to accomplish by the standard 12-lead ECG. Early detection of posterior wall involvement in an inferior myocardial infarction is of paramount importance for the therapeutic outcome. The aim of this study is to assess the role of ST segment elevation in posterior wall leads (V7, V8, V9) on the admission ECG of acute inferior myocardial infarction, for the diagnosis of posterior wall myocardial infarction and the identification of infarct related artery as well as in-hospital outcome following thrombolysis.Methods: A total of 90 patients with acute inferior MI were enrolled by purposive sampling. On the basis of ST segment elevation in posterior leads (V7,V8,V9), study subjects were categorized into two groups: 45 patients of acute inferior MI with ST segment elevation in posterior leads as group I and 45 patients of acute inferior MI without ST segment elevation in posterior leads as group II. Coronary angiography was done during index hospital admission. Interpretation of coronary angiogram was done by visual estimation by two cardiologists to assess the severity of coronary artery disease. Severity of coronary stenosis was graded according to the number of major epicardial vessel with significant stenosis by vessel score and Friesinger score. After CAG, patients were evaluated for in hospital adverse outcome like heart block, cardiogenic shock, arrhythmia, and death.Results: Patients of PMI and non PMI groups were similar in terms of age and sex. Smoking and dyslipidemia (p=0.05) were significantly higher in PMI group. Mean RBS and Troponin-I difference were significantly (p